2022
DOI: 10.3390/su14095325
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Investors’ Investment Intention of Sustainability-Related Investment: Evidence from China

Abstract: This paper investigates how investors respond to the COVID-19 pandemic, particularly regarding their intention to invest in sustainability-related investment (SRI) funds. We conduct two experiments online with participants who have experience with stock and fund investments. The first one includes 292 participants, which aims to explore investors’ attitudes and investment intention of different sustainability-related components, and the second one includes 432 participants, which aims to examine how the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…In addition to formal coordination, this cooperation must also be built on mutual trust between the two sectors. Previous studies have indicated that investors' levels of trust are a significant element in determining whether or not they will participate in a particular investment transaction (Kim et al, 2018;Liu et al, 2022;Xu et al, 2022). Indeed, Akhtar and Das (2019) stress that trust influences an investor's decision to invest.…”
Section: Trust In Government and Investor Decision On Pppmentioning
confidence: 99%
“…In addition to formal coordination, this cooperation must also be built on mutual trust between the two sectors. Previous studies have indicated that investors' levels of trust are a significant element in determining whether or not they will participate in a particular investment transaction (Kim et al, 2018;Liu et al, 2022;Xu et al, 2022). Indeed, Akhtar and Das (2019) stress that trust influences an investor's decision to invest.…”
Section: Trust In Government and Investor Decision On Pppmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic has witnessed a notable trend wherein consumer preferences have increasingly gravitated towards green assets and green products. The study conducted by Xu et al (2022) examines the interplay between the COVID-19 pandemic and the specific category of socially responsible investment (SRI) funds, and its impact on investors' inclination towards investing in SRI funds". Their research reveals that, in the face of the pandemic threat, there is a notable inclination among investors to allocate their funds towards socially responsible investment (SRI) options.…”
Section: Introductionmentioning
confidence: 99%